THE EFFECT OF GREEN ACCOUNTING PRACTICES AND ORGANIZATIONAL SIZE IN BUSINESS SUSTAINABILITY OF PUBLIC HOSPITALS - Muhammad Hasyim Ashari; Yudhi Anggoro (Jurnal Akuntansi, 2021)
To realize business continuity in public hospital institutions, an analysis is needed to be related to the green accounting practices in public hospitals considering the environmental and social impacts caused by their business activities, in addition to the different types (classes) of public hospitals, an analysis is needed regarding the size of the organization of the house. So, this study aims to analyze the effect of green accounting practices and organizational size on business sustainability in public hospitals in Malang Raya. This research is a survey research using descriptive and correlational quantitative approaches. The questionnaire was used to collect data from public hospitals in Malang District, Malang City, and Batu City. A probability sample is used in sample selection with a cluster random sampling technique. The results show that partially the green accounting practices affect business sustainability, while the size of the organization does not affect business sustainability. Simultaneously, the green accounting practices and organizational size has no effect on business sustainability, and this is indicated by the small contribution of the effect of only ten point five percent